Developing a Competency-Based Islamic Religious Education Curriculum in the Era of Independent Learning - Syarif Hidayat; Ingrid Solheim (Muaddib: Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze and formulate a concept for developing a competency-based Islamic Religious Education (PAI) curriculum relevant to the Merdeka Belajar paradigm. The study employed a literature review method, examining various scientific sources, both national and international journals, and current education policy documents. The results indicate that the PAI curriculum in Indonesia is still dominated by a normative-doctrinaire approach that is oriented toward cognitive aspects and teacher-centered, thus less supportive of the realization of freedom of thought and independent learning, as embodied in the spirit of Merdeka Belajar. Based on theoretical analysis, the development of a competency-based PAI curriculum needs to be directed toward integrating spiritual, social, and personal values ​​with 21st-century skills, such as critical thinking, communication, collaboration, and creativity, rooted in Islamic values. This study concludes that transforming the PAI curriculum toward a competency-based model is a strategic step towards building contextual, adaptive Islamic education that is oriented toward character development and holistic competency of students in the Merdeka Belajar era.